2021
DOI: 10.1016/j.cej.2020.127143
|View full text |Cite
|
Sign up to set email alerts
|

3D nanointerface enhanced optical microfiber for real-time detection and sizing of single nanoparticles

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The main sensor detected a single EV in different background solutions that exhibited different variations in the transmission spectra of the main sensor. By observing the step‐wise height of wavelength shift, [ 44 ] the size of PC exosomes in pure PBS and serum solution was mainly distributed in the range of 60–100 nm. However, the main sensor could mainly detect single microvesicle with a size of more than 150 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The main sensor detected a single EV in different background solutions that exhibited different variations in the transmission spectra of the main sensor. By observing the step‐wise height of wavelength shift, [ 44 ] the size of PC exosomes in pure PBS and serum solution was mainly distributed in the range of 60–100 nm. However, the main sensor could mainly detect single microvesicle with a size of more than 150 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid and accurate detection of analytes (nucleic acids, proteins, viruses) at small concentrations is crucial in applications ranging from clinical diagnostics to environmental sensor. [23] It may also enhance the PTT effect. However, evanescent field enhancement at locations other than the fiber surface may increase the noise signals caused by interfering molecules or temperature changes in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Interface design can enhance the evanescent field of microfibers, thereby improving the light–matter interaction with the target analytes, which inherently improves the sensitivity of the sensor. [ 23 ] It may also enhance the PTT effect. However, evanescent field enhancement at locations other than the fiber surface may increase the noise signals caused by interfering molecules or temperature changes in the solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Chen et al reported a portable optical microfibre sensor functionalized by a plasmonic nanointerface for single-nanoparticle detection and sizing. 24 These optical MNF sensors represent an easy-to-perform platform. However, to isolate a single nanoparticle, the sample must be diluted so that on average less than one particle resides in the effective detection region.…”
Section: Introductionmentioning
confidence: 99%